EULAR/ERA-EDTA Lupus Nephritis Recommendations - Rizzo, Toni (MD Conference Express, 2012)
This article presents the new European League Against Rheumatism/European Renal Association European Dialysis and Transplant Association recommendations for the management of adult lupus nephritis, based on expert opinion and a systematic review of 887 published articles. The level of agreement among experts was excellent, with average scores ranging from 8.6 to 9.7 on a 10-point scale.